Pengaruh Harga, Kualitas Produk, dan Kualitas Pelayanan terhadap Kepuasan Konsumen Kelompok Tani - Vita Nur Tianing; Siswahyudianto (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2022)
Consumer goals are one of the main things in a business. Because by making efforts that can be done, namely continuing to maintain and increase satisfaction with consumers, consumers will more often repurchase an item or service that has been consumed or used. Consumer goals are determined by several things, including price, product quality, and service quality. This study analyzed the effect of price, product quality, and service quality on consumer satisfaction at the